La langue française, un enseignement pour les jeunes filles ? Formation professionnelle et construction des savoirs linguistiques à l’ENS de Sèvres (1881-1925) - Muriel Jorge (Genre & Histoire)
The training given at the girls’ École Normale Supérieure of Sèvres, founded in 1881 in order to train women teachers destined to teach at the recently created secondary schools for girls, is known to be of a lesser scientific level than the one reserved for men teaching at secondary school level. However, in literary education, Sèvres has a class dedicated to the study of the French language, separate from the literature class and given by Sorbonne professors. This class combines teaching and learning methods used in men’s secondary and higher education with Sèvres’s own local practice while confronting students with their professors’ erudition and scientific interests, thus meeting both institutional goals and the students’ intellectual expectations. The present paper tackles the subject based on former students’ testimonies, student papers and preparatory notes made by the first professors.